1998
DOI: 10.1093/humrep/13.suppl_2.1
|View full text |Cite
|
Sign up to set email alerts
|

Semen characteristics and fertility tests required for storage of spermatozoa

Abstract: This review addresses critical issues in the selection of semen donors who are very fertile. Traditional semen parameters have been employed and are still used to assess pre- and post-freeze samples in order to discriminate between donors of high and low fecundity. The most predictive factor is the number of motile spermatozoa per straw and the number of motile spermatozoa inseminated. Nevertheless, no absolute standards for fertile samples can be derived from the basic semen examination. The employment of spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…However, if we class the lot as good, we cannot be very sure of this, and it is possible that the spermatozoa from this donor might not survive freezing very well; thus, a future survival test could well produce worse results. This is in agreement with the conclusions of Barrat et al (1998), who found that when donors were given a second chance after an initial survival test produced borderline unacceptable results, they almost always provided another unacceptable result, when a second ejaculate was tested. Theoretically, if we analyse two straws and decide to accept the lot if both straws are good (n = 2; c = 0), we will have a low probability of rejecting good lots (0.10) and a fairly high one of accepting a defective one (0.60).…”
Section: Sampling Plan For the Freezing Of A Semen Specimensupporting
confidence: 92%
See 1 more Smart Citation
“…However, if we class the lot as good, we cannot be very sure of this, and it is possible that the spermatozoa from this donor might not survive freezing very well; thus, a future survival test could well produce worse results. This is in agreement with the conclusions of Barrat et al (1998), who found that when donors were given a second chance after an initial survival test produced borderline unacceptable results, they almost always provided another unacceptable result, when a second ejaculate was tested. Theoretically, if we analyse two straws and decide to accept the lot if both straws are good (n = 2; c = 0), we will have a low probability of rejecting good lots (0.10) and a fairly high one of accepting a defective one (0.60).…”
Section: Sampling Plan For the Freezing Of A Semen Specimensupporting
confidence: 92%
“…This theoretical study enables us to propose various possible explanations for the different findings of other authors concerning semen donor banks, such as the high variability of results (Carrell et al 2002) or the poor results obtained when a second ejaculate was tested for donors given a second chance after an initial survival test produced borderline unacceptable results (Barrat et al 1998). Scheme for the procedure control within a sperm bank (*If a donation or frozen sample does not meet the acceptance sampling requirements, and there is no valid reason for this (such as noncompliance with sexual abstinence, fever, stress, excessive physical exercise, technical problems, etc.…”
Section: Sampling Plans Per Donormentioning
confidence: 84%
“…Semen collection failure and azoospermia rates were recorded in order to assess the feasibility of sperm freezing in the various groups of pathologies. To discuss the potential use of the frozen sperm samples through Assisted Reproductive Technologies (ART), patients were stratified according to their pathology and to NMSPS categories, defined by a possibly minimal NMSPS required for each strategy: ≥ 4x10 6 for Intra-Uterine Insemination (IUI) [ 17 ], in the range < 4 × 10 6 and ≥2 × 10 6 for conventional In Vitro Fertilization (IVF) and < 2 × 10 6 for Intra Cytoplasmic Sperm Injection (ICSI).…”
Section: Methodsmentioning
confidence: 99%
“…However, there are such differences in the fecundity of men even when ‘reasonable numbers of motile cells’ are present that either the proportion of effective cells in the ejaculate/and or their fecundity is significantly different. Further examples of this relate to donor insemination where fecundity of donors can vary by a factor of 3 even though motile sperm numbers are equal ( Barratt et al , 1998 ).…”
Section: Natural Sperm Selectionmentioning
confidence: 99%